Sol LeWitt : Brick Wall 1977. (New York : Tanglewood Press Inc, 1977)
"Brick Wall consists of sixteen, two-page prints that vary slightly in exposure. The piece surveys the repetition of form and texture to create a more complex whole, and exemplifies the utility of the camera to document processes and series, themes central to conceptual art."
Engels
boek
Keywords: LeWitt, Sol